Design, synthesis and perception of fluorescently labeled isoprenoid cytokinins - Kubiasová, Karolina; Mik, Václav; Nisler, Jaroslav; Hönig, Martin; Husičková, Alexandra; Spíchal, Lukáš; Pěkná, Zuzana; Šamajová, Olga; Doležal, Karel; Plíhal, Ondřej; Benková, Eva; Strnad, Miroslav; et al. (Phytochemistry)
Isoprenoid cytokinins play a number of crucial roles in the regulation of plant growth and development. To study cytokinin receptor properties in plants, we designed and prepared fluorescent derivatives of 6-[(3-methylbut-2-en-1-yl)amino]purine (N6-isopentenyladenine, iP) with several fluorescent labels attached to the C2 or N9 atom of the purine moiety via a 2- or 6-carbon linker. The fluorescent labels included dansyl (DS), fluorescein (FC), 7-nitrobenzofurazan (NBD), rhodamine B (RhoB), coumarin (Cou), 7-(diethylamino)coumarin (DEAC) and cyanine 5 dye (Cy5). All prepared compounds were screened for affinity for the Arabidopsis thaliana cytokinin receptor (CRE1/AHK4). Although the attachment of the fluorescent labels to iP via the linkers mostly disrupted binding to the receptor, several fluorescent derivatives interacted well. For this reason, three derivatives, two rhodamine B and one 4-chloro-7-nitrobenzofurazan labeled iP were tested for their interaction with CRE1/AHK4 and Zea mays cytokinin receptors in detail. We further showed that the three derivatives were able to activate transcription of cytokinin response regulator ARR5 in Arabidopsis seedlings. The activity of fluorescently labeled cytokinins was compared with corresponding 6-dimethylaminopurine fluorescently labeled negative controls. Selected rhodamine B C2-labeled compounds 17, 18 and 4-chloro-7-nitrobenzofurazan N9-labeled compound 28 and their respective negative controls (19, 20 and 29, respectively) were used for in planta staining experiments in Arabidopsis thaliana cell suspension culture using live cell confocal microscopy.

Mutations in blind cavefish target the light regulated circadian clock gene period 2 - Ceinos, Rosa Maria; Frigato, Elena; Pagano, Cristina; Frohlich, Nadine; Negrini, Pietro; Cavallari, Nicola; Vallone, Daniela; Fuselli, Silvia; Bertolucci, Cristiano; Foulkes, Nicholas S (Scientific Reports)
Light represents the principal signal driving circadian clock entrainment. However, how light influences the evolution of the clock remains poorly understood. The cavefish Phreatichthys andruzzii represents a fascinating model to explore how evolution under extreme aphotic conditions shapes the circadian clock, since in this species the clock is unresponsive to light. We have previously demonstrated that loss-of-function mutations targeting non-visual opsins contribute in part to this blind clock phenotype. Here, we have compared orthologs of two core clock genes that play a key role in photic entrainment, cry1a and per2, in both zebrafish and P. andruzzii. We encountered aberrantly spliced variants for the P. andruzzii per2 transcript. The most abundant transcript encodes a truncated protein lacking the C-terminal Cry binding domain and incorporating an intronic, transposon-derived coding sequence. We demonstrate that the transposon insertion leads to a predominantly cytoplasmic localization of the cavefish Per2 protein in contrast to the zebrafish ortholog which is distributed in both the nucleus and cytoplasm. Thus, it seems that during evolution in complete darkness, the photic entrainment pathway of the circadian clock has been subject to mutation at multiple levels, extending from opsin photoreceptors to nuclear effectors.

The cyclin‐dependent kinase G group defines a thermo‐sensitive alternative splicing circuit modulating the expression of Arabidopsis ATU 2AF 65A - Cavallari, Nicola; Nibau, Candida; Fuchs, Armin; Dadarou, Despoina; Barta, Andrea; Doonan, John (The Plant Journal)
The ability to adapt growth and development to temperature variations is crucial to generate plant varieties resilient to predicted temperature changes. However, the mechanisms underlying plant response to progressive increases in temperature have just started to be elucidated. Here, we report that the Cyclin-dependent Kinase G1 (CDKG1) is a central element in a thermo-sensitive mRNA splicing cascade that transduces changes in ambient temperature into differential expression of the fundamental spliceosome component, ATU2AF65A. CDKG1 is alternatively spliced in a temperature-dependent manner. We found that this process is partly dependent on both the Cyclin-dependent Kinase G2 (CDKG2) and the interacting co-factor CYCLIN L1 resulting in two distinct messenger RNAs. Relative abundance of both CDKG1 transcripts correlates with ambient temperature and possibly with different expression levels of the associated protein isoforms. Both CDKG1 alternative transcripts are necessary to fully complement the expression of ATU2AF65A across the temperature range. Our data support a previously unidentified temperature-dependent mechanism based on the alternative splicing of CDKG1 and regulated by CDKG2 and CYCLIN L1. We propose that changes in ambient temperature affect the relative abundance of CDKG1 transcripts and this in turn translates into differential CDKG1 protein expression coordinating the alternative splicing of ATU2AF65A. This article is protected by copyright. All rights reserved.

Identification and characterization of novel auxin-cytokinin cross-talk components - Hurny, Andrej
The whole life cycle of plants as well as their responses to environmental stimuli is governed by a complex network of hormonal regulations. A number of studies have demonstrated an essential role of both auxin and cytokinin in the regulation of many aspects of plant growth and development including embryogenesis, postembryonic organogenic processes such as root, and shoot branching, root and shoot apical meristem activity and phyllotaxis. Over the last decades essential knowledge on the key molecular factors and pathways that spatio-temporally define auxin and cytokinin activities in the plant body has accumulated. However, how both hormonal pathways are interconnected by a complex network of interactions and feedback circuits that determines the final outcome of the individual hormone actions is still largely unknown. Root system architecture establishment and in particular formation of lateral organs is prime example of developmental process at whose regulation both auxin and cytokinin pathways converge. To dissect convergence points and pathways that tightly balance auxin - cytokinin antagonistic activities that determine the root branching pattern transcriptome profiling was applied. Genome wide expression analyses of the xylem pole pericycle, a tissue giving rise to lateral roots, led to identification of genes that are highly responsive to combinatorial auxin and cytokinin treatments and play an essential function in the auxin-cytokinin regulated root branching. SYNERGISTIC AUXIN CYTOKININ 1 (SYAC1) gene, which encodes for a protein of unknown function, was detected among the top candidate genes of which expression was synergistically up-regulated by simultaneous hormonal treatment. Plants with modulated SYAC1 activity exhibit severe defects in the root system establishment and attenuate developmental responses to both auxin and cytokinin. To explore the biological function of the SYAC1, we employed different strategies including expression pattern analysis, subcellular localization and phenotypic analyses of the syac1 loss-of-function and gain-of-function transgenic lines along with the identification of the SYAC1 interaction partners. Detailed functional characterization revealed that SYAC1 acts as a developmentally specific regulator of the secretory pathway to control deposition of cell wall components and thereby rapidly fine tune elongation growth.

PID/WAG-mediated phosphorylation of the Arabidopsis PIN3 auxin transporter mediates polarity switches during gravitropism - Grones, Peter; Abas, Melinda F; Hajny, Jakub; Jones, Angharad; Waidmann, Sascha; Kleine Vehn, Jürgen; Friml, Jirí (Scientific Reports)
Intercellular distribution of the plant hormone auxin largely depends on the polar subcellular distribution of the plasma membrane PIN-FORMED (PIN) auxin transporters. PIN polarity switches in response to different developmental and environmental signals have been shown to redirect auxin fluxes mediating certain developmental responses. PIN phosphorylation at different sites and by different kinases is crucial for PIN function. Here we investigate the role of PIN phosphorylation during gravitropic response. Loss- and gain-of-function mutants in PINOID and related kinases but not in D6PK kinase as well as mutations mimicking constitutive dephosphorylated or phosphorylated status of two clusters of predicted phosphorylation sites partially disrupted PIN3 phosphorylation and caused defects in gravitropic bending in roots and hypocotyls. In particular, they impacted PIN3 polarity rearrangements in response to gravity and during feed-back regulation by auxin itself. Thus PIN phosphorylation, besides regulating transport activity and apical-basal targeting, is also important for the rapid polarity switches in response to environmental and endogenous signals.

Transporters and mechanisms of hormone transport in arabidopsis - Abualia, Rashed; Benková, Eva; Lacombe, Benoît (Advances in Botanical Research)
Plant hormones as signalling molecules play an essential role in the control of plant growth and development. Typically, sites of hormonal action are usually distant from the site of biosynthesis thus relying on efficient transport mechanisms. Over the last decades, molecular identification of proteins and protein complexes involved in hormonal transport has started. Advanced screens for genes involved in hormonal transport in combination with transport assays using heterologous systems such as yeast, insect, or tobacco BY2 cells or Xenopus oocytes provided important insights into mechanisms underlying distribution of hormones in plant body and led to identification of principal transporters for each hormone. This review gives a short overview of the mechanisms of hormonal transport and transporters identified in Arabidopsis thaliana.

Light regulated expression of sensor histidine kinase CKI1 controls cytokinin related development - Dobisova, Tereza; Hrdinova, Vendula; Cuesta, Candela; Michlickova, Sarka; Urbankova, Ivana; Hejatkova, Romana; Zadnikova, Petra; Pernisová, Markéta; Benková, Eva; Hejátko, Jan (Plant Physiology)
In plants, the multistep phosphorelay (MSP) pathway mediates a range of regulatory processes, including those activated by cytokinins. The crosstalk between cytokinin response and light is known for a long time. However, the molecular mechanism underlying the interactionbetween light and cytokinin signaling remains elusive. In the screen for upstream regulators we identified a LONG PALE HYPOCOTYL (LPH) gene whose activity is indispensable for spatiotemporally correct expression of CYTOKININ INDEPENDENT-1 (CKI1), encoding the constitutively active sensor histidine kinase that activates MSP signaling. lph is a new allele of HEME OXYGENASE 1 (HY1) which encodes the key protein in the biosynthesis of phytochromobilin, a cofactor of photoconvertiblephytochromes. Our analysis confirmed the light-dependent regulation oftheCKI1 expression pattern. We show that CKI1 expression is under the control of phytochrome A (phyA), functioning as a dual (both positive and negative) regulator of CKI1 expression, presumably via the phyA-regulated transcription factors PHYTOCHROME INTERACTING FACTOR 3 (PIF3) and CIRCADIAN CLOCK ASSOCIATED 1 (CCA1). Changes in CKI1 expression observed in lph/hy1-7 and phy mutants correlatewithmisregulation of MSP signaling, changedcytokinin sensitivity and developmental aberrations,previously shown to be associated with cytokinin and/or CKI1 action. Besides that, we demonstrate novel role of phyA-dependent CKI1 expression in the hypocotyl elongation and hook development during skotomorphogenesis. Based on these results, we propose that the light-dependent regulation of CKI1 provides a plausible mechanistic link underlying the well-known interaction between light- and cytokinin-controlled plant development.

Spatiotemporal mechanisms of root branching - Ötvös, Krisztina; Benková, Eva (Current Opinion in Genetics & Development)
The fundamental tasks of the root system are, besides anchoring, mediating interactions between plant and soil and providing the plant with water and nutrients. The architecture of the root system is controlled by endogenous mechanisms that constantly integrate environmental signals, such as availability of nutrients and water. Extremely important for efficient soil exploitation and survival under less favorable conditions is the developmental flexibility of the root system that is largely determined by its postembryonic branching capacity. Modulation of initiation and outgrowth of lateral roots provides roots with an exceptional plasticity, allows optimal adjustment to underground heterogeneity, and enables effective soil exploitation and use of resources. Here we discuss recent advances in understanding the molecular mechanisms that shape the plant root system and integrate external cues to adapt to the changing environment.

Live tracking of moving samples in confocal microscopy for vertically grown roots - Von Wangenheim, Daniel; Hauschild, Robert; Fendrych, Matyas; Barone, Vanessa; Benková, Eva; Friml, Jirí (eLife)
Roots navigate through soil integrating environmental signals to orient their growth. The Arabidopsis root is a widely used model for developmental, physiological and cell biological studies. Live imaging greatly aids these efforts, but the horizontal sample position and continuous root tip displacement present significant difficulties. Here, we develop a confocal microscope setup for vertical sample mounting and integrated directional illumination. We present TipTracker – a custom software for automatic tracking of diverse moving objects usable on various microscope setups. Combined, this enables observation of root tips growing along the natural gravity vector over prolonged periods of time, as well as the ability to induce rapid gravity or light stimulation. We also track migrating cells in the developing zebrafish embryo, demonstrating the utility of this system in the acquisition of high-resolution data sets of dynamic samples. We provide detailed descriptions of the tools enabling the easy implementation on other microscopes.

Methodological advances in auxin and cytokinin biology - Hurny, Andrej; Benková, Eva (Auxins and Cytokinins in Plant Biology)
The history of auxin and cytokinin biology including the initial discoveries by father–son duo Charles Darwin and Francis Darwin (1880), and Gottlieb Haberlandt (1919) is a beautiful demonstration of unceasing continuity of research. Novel findings are integrated into existing hypotheses and models and deepen our understanding of biological principles. At the same time new questions are triggered and hand to hand with this new methodologies are developed to address these new challenges.

Cellular mechanisms for cargo delivery and polarity maintenance at different polar domains in plant cells - Łangowski, Łukasz; Wabnik, Krzysztof T; Li, Hongjiang; Vanneste, Steffen; Naramoto, Satoshi; Tanaka, Hirokazu; Friml, Jirí (Cell Discovery)
The asymmetric localization of proteins in the plasma membrane domains of eukaryotic cells is a fundamental manifestation of cell polarity that is central to multicellular organization and developmental patterning. In plants, the mechanisms underlying the polar localization of cargo proteins are still largely unknown and appear to be fundamentally distinct from those operating in mammals. Here, we present a systematic, quantitative comparative analysis of the polar delivery and subcellular localization of proteins that characterize distinct polar plasma membrane domains in plant cells. The combination of microscopic analyses and computational modeling revealed a mechanistic framework common to diverse polar cargos and underlying the establishment and maintenance of apical, basal, and lateral polar domains in plant cells. This mechanism depends on the polar secretion, constitutive endocytic recycling, and restricted lateral diffusion of cargos within the plasma membrane. Moreover, our observations suggest that polar cargo distribution involves the individual protein potential to form clusters within the plasma membrane and interact with the extracellular matrix. Our observations provide insights into the shared cellular mechanisms of polar cargo delivery and polarity maintenance in plant cells.

A model of differential growth guided apical hook formation in plants - Žádníková, Petra; Wabnik, Krzysztof T; Abuzeineh, Anas; Gallemí, Marçal; Van Der Straeten, Dominique; Smith, Richard; Inze, Dirk; Friml, Jirí; Prusinkiewicz, Przemysław; Benková, Eva (Plant Cell)
Differential cell growth enables flexible organ bending in the presence of environmental signals such as light or gravity. A prominent example of the developmental processes based on differential cell growth is the formation of the apical hook that protects the fragile shoot apical meristem when it breaks through the soil during germination. Here, we combined in silico and in vivo approaches to identify a minimal mechanism producing auxin gradient-guided differential growth during the establishment of the apical hook in the model plant Arabidopsis thaliana. Computer simulation models based on experimental data demonstrate that asymmetric expression of the PIN-FORMED auxin efflux carrier at the concave (inner) versus convex (outer) side of the hook suffices to establish an auxin maximum in the epidermis at the concave side of the apical hook. Furthermore, we propose a mechanism that translates this maximum into differential growth, and thus curvature, of the apical hook. Through a combination of experimental and in silico computational approaches, we have identified the individual contributions of differential cell elongation and proliferation to defining the apical hook and reveal the role of auxin-ethylene crosstalk in balancing these two processes. © 2016 American Society of Plant Biologists. All rights reserved.

Cytokinin response factors integrate auxin and cytokinin pathways for female reproductive organ development - Cucinotta, Mara; Manrique, Silvia; Guazzotti, Andrea; Quadrelli, Nadia; Mendes, Marta; Benková, Eva; Colombo, Lucia (Development)
The developmental programme of the pistil is under the control of both auxin and cytokinin. Crosstalk between these factors converges on regulation of the auxin carrier PIN-FORMED 1 (PIN1). Here, we show that in the triple transcription factor mutant cytokinin response factor 2 (crf2) crf3 crf6 both pistil length and ovule number were reduced. PIN1 expression was also lower in the triple mutant and the phenotypes could not be rescued by exogenous cytokinin application. pin1 complementation studies using genomic PIN1 constructs showed that the pistil phenotypes were only rescued when the PCRE1 domain, to which CRFs bind, was present. Without this domain, pin mutants resemble the crf2 crf3 crf6 triple mutant, indicating the pivotal role of CRFs in auxin-cytokinin crosstalk.

Real time analysis of the apical hook development - Zhu, Qiang; Žádníková, Petra; Smet, Dajo; Van Der Straeten, Dominique; Benková, Eva (Plant Hormones)
Mechanisms for cell protection are essential for survival of multicellular organisms. In plants, the apical hook, which is transiently formed in darkness when the germinating seedling penetrates towards the soil surface, plays such protective role and shields the vitally important shoot apical meristem and cotyledons from damage. The apical hook is formed by bending of the upper hypocotyl soon after germination, and it is maintained in a closed stage while the hypocotyl continues to penetrate through the soil and rapidly opens when exposed to light in proximity of the soil surface. To uncover the complex molecular network orchestrating this spatiotemporally tightly coordinated process, monitoring of the apical hook development in real time is indispensable. Here we describe an imaging platform that enables high-resolution kinetic analysis of this dynamic developmental process. © Springer Science+Business Media New York 2017.

DRACULA2 is a dynamic nucleoporin with a role in regulating the shade avoidance syndrome in Arabidopsis - Gallemi Rovira, Marcal; Galstyan, Anahit; Paulišić, Sandi; Then, Christiane; Ferrández Ayela, Almudena; Lorenzo Orts, Laura; Roig Villanova, Irma; Wang, Xuewen; Micol, José; Ponce, Maria; Devlin, Paul; Martínez García, Jaime (Development)
When plants grow in close proximity basic resources such as light can become limiting. Under such conditions plants respond to anticipate and/or adapt to the light shortage, a process known as the shade avoidance syndrome (SAS). Following genetic screening using a shade-responsive luciferase reporter line (PHYB:LUC), we identified DRACULA2 (DRA2), which encodes an Arabidopsis homolog of mammalian nucleoporin 98, a component of the nuclear pore complex (NPC). DRA2, together with other nucleoporins, participates positively in the control of the hypocotyl elongation response to plant proximity, a role that can be considered dependent on the nucleocytoplasmic transport of macromolecules (i.e. is transport dependent). In addition, our results reveal a specific role for DRA2 in controlling shade-induced gene expression. We suggest that this novel regulatory role of DRA2 is transport independent and that it might rely on its dynamic localization within and outside of the NPC. These results provide mechanistic insights in to how SAS responses are rapidly established by light conditions. They also indicate that nucleoporins have an active role in plant signaling.

Sorting motifs involved in the trafficking and localization of the PIN1 auxin efflux carrier - Sancho Andrés, Gloria; Soriano Ortega, Esther; Gao, Caiji; Bernabé Orts, Joan; Narasimhan, Madhumitha; Müller, Anna; Tejos, Ricardo; Jiang, Liwen; Friml, Jirí; Aniento, Fernando; Marcote, Maria (Plant Physiology)
n contrast with the wealth of recent reports about the function of μ-adaptins and clathrin adaptor protein (AP) complexes, there is very little information about the motifs that determine the sorting of membrane proteins within clathrin-coated vesicles in plants. Here, we investigated putative sorting signals in the large cytosolic loop of the Arabidopsis (Arabidopsis thaliana) PIN-FORMED1 (PIN1) auxin transporter, which are involved in binding μ-adaptins and thus in PIN1 trafficking and localization. We found that Phe-165 and Tyr-280, Tyr-328, and Tyr-394 are involved in the binding of different μ-adaptins in vitro. However, only Phe-165, which binds μA(μ2)- and μD(μ3)-adaptin, was found to be essential for PIN1 trafficking and localization in vivo. The PIN1:GFP-F165A mutant showed reduced endocytosis but also localized to intracellular structures containing several layers of membranes and endoplasmic reticulum (ER) markers, suggesting that they correspond to ER or ER-derived membranes. While PIN1:GFP localized normally in a μA (μ2)-adaptin mutant, it accumulated in big intracellular structures containing LysoTracker in a μD (μ3)-adaptin mutant, consistent with previous results obtained with mutants of other subunits of the AP-3 complex. Our data suggest that Phe-165, through the binding of μA (μ2)- and μD (μ3)-adaptin, is important for PIN1 endocytosis and for PIN1 trafficking along the secretory pathway, respectively.

Mapping the subcellular mechanical properties of live cells in tissues with fluorescence emission-Brillouin imaging - Elsayad, Kareem; Werner, Stephanie; Gallemi Rovira, Marcal; Kong, Jixiang; Guajardo, Edmundo; Zhang, Lijuan; Jaillais, Yvon; Greb, Thomas; Belkhadir, Youssef (Science Signaling)
Extracellular matrices (ECMs) are central to the advent of multicellular life, and their mechanical propertiesare modulated by and impinge on intracellular signaling pathways that regulate vital cellular functions. High spatial-resolution mapping of mechanical properties in live cells is, however, extremely challenging. Thus, our understanding of how signaling pathways process physiological signals to generate appropriate mechanical responses is limited. We introduce fluorescence emission-Brillouin scattering imaging (FBi), a method for the parallel and all-optical measurements of mechanical properties and fluorescence at the submicrometer scale in living organisms. Using FBi, we showed thatchanges in cellular hydrostatic pressure and cytoplasm viscoelasticity modulate the mechanical signatures of plant ECMs. We further established that the measured "stiffness" of plant ECMs is symmetrically patternedin hypocotyl cells undergoing directional growth. Finally, application of this method to Arabidopsis thaliana with photoreceptor mutants revealed that red and far-red light signals are essential modulators of ECM viscoelasticity. By mapping the viscoelastic signatures of a complex ECM, we provide proof of principlefor the organism-wide applicability of FBi for measuring the mechanical outputs of intracellular signaling pathways. As such, our work has implications for investigations of mechanosignaling pathways and developmental biology.

Plant hormones in interactions with the environment - Benková, Eva (Plant Molecular Biology)
Plants are continuously exposed to a myriad of external signals such as fluctuating nutrients availability, drought, heat, cold, high salinity, or pathogen/pest attacks that can severely affect their development, growth, and fertility. As sessile organisms, plants must therefore be able to sense and rapidly react to these external inputs, activate efficient responses, and adjust development to changing conditions. In recent years, significant progress has been made towards understanding the molecular mechanisms underlying the intricate and complex communication between plants and the environment. It is now becoming increasingly evident that hormones have an important regulatory role in plant adaptation and defense mechanisms.

Lateral root emergence in Arabidopsis is dependent on transcription factor LBD29 regulation of auxin influx carrier LAX3 - Porco, Silvana; Larrieu, Antoine; Du, Yujuan; Gaudinier, Allison; Goh, Tatsuaki; Swarup, Kamal; Swarup, Ranjan; Kuempers, Britta; Bishopp, Anthony; Lavenus, Julien; Casimiro, Ilda; Hill, Kristine; et al. (Development)
Lateral root primordia (LRP) originate from pericycle stem cells located deep within parental root tissues. LRP emerge through overlying root tissues by inducing auxin-dependent cell separation and hydraulic changes in adjacent cells. The auxin-inducible auxin influx carrier LAX3 plays a key role concentrating this signal in cells overlying LRP. Delimiting LAX3 expression to two adjacent cell files overlying new LRP is crucial to ensure that auxin-regulated cell separation occurs solely along their shared walls. Multiscale modeling has predicted that this highly focused pattern of expression requires auxin to sequentially induce auxin efflux and influx carriers PIN3 and LAX3, respectively. Consistent with model predictions, we report that auxin-inducible LAX3 expression is regulated indirectly by AUXIN RESPONSE FACTOR 7 (ARF7). Yeast one-hybrid screens revealed that the LAX3 promoter is bound by the transcription factor LBD29, which is a direct target for regulation by ARF7. Disrupting auxin-inducible LBD29 expression or expressing an LBD29-SRDX transcriptional repressor phenocopied the lax3 mutant, resulting in delayed lateral root emergence. We conclude that sequential LBD29 and LAX3 induction by auxin is required to coordinate cell separation and organ emergence.

Nitrate controls root development through posttranscriptional regulation of the NRT1.1/NPF6.3 transporter sensor - Bouguyon, Eléonore; Perrine Walker, Francine; Pervent, Marjorie; Rochette, Juliette; Cuesta, Candela; Benková, Eva; Martinière, Alexandre; Bach, Lien; Krouk, Gabriel; Gojon, Alain; Nacry, Philippe (Plant Physiology)
Plants are able to modulate root growth and development to optimize their nitrogen nutrition. In Arabidopsis (Arabidopsis thaliana), the adaptive root response to nitrate (NO3 -) depends on the NRT1.1/NPF6.3 transporter/sensor. NRT1.1 represses emergence of lateral root primordia (LRPs) at low concentration or absence of NO3 - through its auxin transport activity that lowers auxin accumulation in LR. However, these functional data strongly contrast with the known transcriptional regulation of NRT1.1, which is markedly repressed in LRPs in the absence of NO3 -. To explain this discrepancy, we investigated in detail the spatiotemporal expression pattern of the NRT1.1 protein during LRP development and combined local transcript analysis with the use of transgenic lines expressing tagged NRT1.1 proteins. Our results show that although NO3 - stimulates NRT1.1 transcription and probably mRNA stability both in primary root tissues and in LRPs, it acts differentially on protein accumulation, depending on the tissues considered with stimulation in cortex and epidermis of the primary root and a strong repression in LRPs and to a lower extent at the primary root tip. This demonstrates that NRT1.1 is strongly regulated at the posttranscriptional level by tissue-specific mechanisms. These mechanisms are crucial for controlling the large palette of adaptive responses to NO3 - mediated by NRT1.1 as they ensure that the protein is present in the proper tissue under the specific conditions where it plays a signaling role in this particular tissue.

Seedlings’ strategy to overcome a soil barrier - Zhu, Qiang; Benková, Eva (Trends in Plant Science)
The impact of the plant hormone ethylene on seedling development has long been recognized; however, its ecophysiological relevance is unexplored. Three recent studies demonstrate that ethylene is a critical endogenous integrator of various environmental signals including mechanical stress, light, and oxygen availability during seedling germination and growth through the soil.

Cytokinin response factor 6 represses cytokinin-associated genes during oxidative stress - Zwack, Paul; De Clercq, Inge; Howton, Timothy; Hallmark, H Tucker; Hurny, Andrej; Keshishian, Erika; Parish, Alyssa; Benková, Eva; Mukhtar, M Shahid; Van Breusegem, Frank; Rashotte, Aaron (Plant Physiology)
Cytokinin is a phytohormone that is well known for its roles in numerous plant growth and developmental processes, yet it has also been linked to abiotic stress response in a less defined manner. Arabidopsis (Arabidopsis thaliana) Cytokinin Response Factor 6 (CRF6) is a cytokinin-responsive AP2/ERF-family transcription factor that, through the cytokinin signaling pathway, plays a key role in the inhibition of dark-induced senescence. CRF6 expression is also induced by oxidative stress, and here we show a novel function for CRF6 in relation to oxidative stress and identify downstream transcriptional targets of CRF6 that are repressed in response to oxidative stress. Analysis of transcriptomic changes in wild-type and crf6 mutant plants treated with H2O2 identified CRF6-dependent differentially expressed transcripts, many of which were repressed rather than induced. Moreover, many repressed genes also show decreased expression in 35S:CRF6 overexpressing plants. Together, these findings suggest that CRF6 functions largely as a transcriptional repressor. Interestingly, among the H2O2 repressed CRF6-dependent transcripts was a set of five genes associated with cytokinin processes: (signaling) ARR6, ARR9, ARR11, (biosynthesis) LOG7, and (transport) ABCG14. We have examined mutants of these cytokinin-associated target genes to reveal novel connections to oxidative stress. Further examination of CRF6-DNA interactions indicated that CRF6 may regulate its targets both directly and indirectly. Together, this shows that CRF6 functions during oxidative stress as a negative regulator to control this cytokinin-associated module of CRF6- dependent genes and establishes a novel connection between cytokinin and oxidative stress response.

Targeted cell elimination reveals an auxin-guided biphasic mode of lateral root initiation - Marhavy, Peter; Montesinos López, Juan C; Abuzeineh, Anas; Van Damme, Daniël; Vermeer, Joop; Duclercq, Jérôme; Rakusova, Hana; Marhavá, Petra; Friml, Jirí; Geldner, Niko; Benková, Eva (Genes and Development)
To sustain a lifelong ability to initiate organs, plants retain pools of undifferentiated cells with a preserved prolif eration capacity. The root pericycle represents a unique tissue with conditional meristematic activity, and its tight control determines initiation of lateral organs. Here we show that the meristematic activity of the pericycle is constrained by the interaction with the adjacent endodermis. Release of these restraints by elimination of endo dermal cells by single-cell ablation triggers the pericycle to re-enter the cell cycle. We found that endodermis removal substitutes for the phytohormone auxin-dependent initiation of the pericycle meristematic activity. However, auxin is indispensable to steer the cell division plane orientation of new organ-defining divisions. We propose a dual, spatiotemporally distinct role for auxin during lateral root initiation. In the endodermis, auxin releases constraints arising from cell-to-cell interactions that compromise the pericycle meristematic activity, whereas, in the pericycle, auxin defines the orientation of the cell division plane to initiate lateral roots.

Vascular cambium regeneration and vessel formation in wounded inflorescence stems of Arabidopsis - Mazur, Ewa; Benková, Eva; Friml, Jirí (Scientific Reports)
Synchronized tissue polarization during regeneration or de novo vascular tissue formation is a plant-specific example of intercellular communication and coordinated development. According to the canalization hypothesis, the plant hormone auxin serves as polarizing signal that mediates directional channel formation underlying the spatio-temporal vasculature patterning. A necessary part of canalization is a positive feedback between auxin signaling and polarity of the intercellular auxin flow. The cellular and molecular mechanisms of this process are still poorly understood, not the least, because of a lack of a suitable model system. We show that the main genetic model plant, Arabidopsis (Arabidopsis thaliana) can be used to study the canalization during vascular cambium regeneration and new vasculature formation. We monitored localized auxin responses, directional auxin-transport channels formation, and establishment of new vascular cambium polarity during regenerative processes after stem wounding. The increased auxin response above and around the wound preceded the formation of PIN1 auxin transporter-marked channels from the primarily homogenous tissue and the transient, gradual changes in PIN1 localization preceded the polarity of newly formed vascular tissue. Thus, Arabidopsis is a useful model for studies of coordinated tissue polarization and vasculature formation after wounding allowing for genetic and mechanistic dissection of the canalization hypothesis.

The importance of localized auxin production for morphogenesis of reproductive organs and embryos in Arabidopsis - Robert, Hélène; Crhák Khaitová, Lucie; Mroue, Souad; Benková, Eva (Journal of Experimental Botany)
Plant sexual reproduction involves highly structured and specialized organs: stamens (male) and gynoecia (female, containing ovules). These organs synchronously develop within protective flower buds, until anthesis, via tightly coordinated mechanisms that are essential for effective fertilization and production of viable seeds. The phytohormone auxin is one of the key endogenous signalling molecules controlling initiation and development of these, and other, plant organs. In particular, its uneven distribution, resulting from tightly controlled production, metabolism and directional transport, is an important morphogenic factor. In this review we discuss how developmentally controlled and localized auxin biosynthesis and transport contribute to the coordinated development of plants' reproductive organs, and their fertilized derivatives (embryos) via the regulation of auxin levels and distribution within and around them. Current understanding of the links between de novo local auxin biosynthesis, auxin transport and/or signalling is presented to highlight the importance of the non-cell autonomous action of auxin production on development and morphogenesis of reproductive organs and embryos. An overview of transcription factor families, which spatiotemporally define local auxin production by controlling key auxin biosynthetic enzymes, is also presented.

A coherent transcriptional feed-forward motif model for mediating auxin-sensitive PIN3 expression during lateral root development - Chen, Qian; Liu, Yang; Maere, Steven; Lee, Eunkyoung; Van Isterdael, Gert; Xie, Zidian; Xuan, Wei; Lucas, Jessica; Vassileva, Valya; Kitakura, Saeko; Marhavy, Peter; Wabnik, Krzysztof T; et al. (Nature Communications)
Multiple plant developmental processes, such as lateral root development, depend on auxin distribution patterns that are in part generated by the PIN-formed family of auxin-efflux transporters. Here we propose that AUXIN RESPONSE FACTOR7 (ARF7) and the ARF7-regulated FOUR LIPS/MYB124 (FLP) transcription factors jointly form a coherent feed-forward motif that mediates the auxin-responsive PIN3 transcription in planta to steer the early steps of lateral root formation. This regulatory mechanism might endow the PIN3 circuitry with a temporal 'memory' of auxin stimuli, potentially maintaining and enhancing the robustness of the auxin flux directionality during lateral root development. The cooperative action between canonical auxin signalling and other transcription factors might constitute a general mechanism by which transcriptional auxin-sensitivity can be regulated at a tissue-specific level.

Strategies of seedlings to overcome their sessile nature: Auxin in mobility control - Žádníková, Petra; Smet, Dajo; Zhu, Qiang; Van Der Straeten, Dominique; Benková, Eva (Frontiers in Plant Science)
Plants are sessile organisms that are permanently restricted to their site of germination. To compensate for their lack of mobility, plants evolved unique mechanisms enabling them to rapidly react to ever changing environmental conditions and flexibly adapt their postembryonic developmental program. A prominent demonstration of this developmental plasticity is their ability to bend organs in order to reach the position most optimal for growth and utilization of light, nutrients, and other resources. Shortly after germination, dicotyledonous seedlings form a bended structure, the so-called apical hook, to protect the delicate shoot meristem and cotyledons from damage when penetrating through the soil. Upon perception of a light stimulus, the apical hook rapidly opens and the photomorphogenic developmental program is activated. After germination, plant organs are able to align their growth with the light source and adopt the most favorable orientation through bending, in a process named phototropism. On the other hand, when roots and shoots are diverted from their upright orientation, they immediately detect a change in the gravity vector and bend to maintain a vertical growth direction. Noteworthy, despite the diversity of external stimuli perceived by different plant organs, all plant tropic movements share a common mechanistic basis: differential cell growth. In our review, we will discuss the molecular principles underlying various tropic responses with the focus on mechanisms mediating the perception of external signals, transduction cascades and downstream responses that regulate differential cell growth and consequently, organ bending. In particular, we highlight common and specific features of regulatory pathways in control of the bending of organs and a role for the plant hormone auxin as a key regulatory component.

Cytokinin response factors regulate PIN-FORMED auxin transporters - Šimášková, Mária; O'Brien, José; Khan-Djamei, Mamoona; Van Noorden, Giel; Ötvös, Krisztina; Vieten, Anne; De Clercq, Inge; Van Haperen, Johanna; Cuesta, Candela; Hoyerová, Klára; Vanneste, Steffen; Marhavy, Peter; et al. (Nature Communications)
Auxin and cytokinin are key endogenous regulators of plant development. Although cytokinin-mediated modulation of auxin distribution is a developmentally crucial hormonal interaction, its molecular basis is largely unknown. Here we show a direct regulatory link between cytokinin signalling and the auxin transport machinery uncovering a mechanistic framework for cytokinin-auxin cross-talk. We show that the CYTOKININ RESPONSE FACTORS (CRFs), transcription factors downstream of cytokinin perception, transcriptionally control genes encoding PIN-FORMED (PIN) auxin transporters at a specific PIN CYTOKININ RESPONSE ELEMENT (PCRE) domain. Removal of this cis-regulatory element effectively uncouples PIN transcription from the CRF-mediated cytokinin regulation and attenuates plant cytokinin sensitivity. We propose that CRFs represent a missing cross-talk component that fine-tunes auxin transport capacity downstream of cytokinin signalling to control plant development.

Auxin and Its Role in Plant Development
Auxin is an important signaling compound in plants and vital for plant development and growth. The present book, Auxin and its Role in Plant Development, provides the reader with detailed and comprehensive insight into the functioning of the molecule on the whole and specifically in plant development. In the first part, the functioning, metabolism and signaling pathways of auxin in plants are explained, the second part depicts the specific role of auxin in plant development and the third part describes the interaction and functioning of the signaling compound upon stimuli of the environment. Each chapter is written by international experts in the respective field and designed for scientists and researchers in plant biology, plant development and cell biology to summarize the recent progress in understanding the role of auxin and suggest future perspectives for auxin research.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

Dynamic infrared imaging analysis of apical hook development in Arabidopsis: The case of brassinosteroids - Smet, Dajo; Žádníková, Petra; Vandenbussche, Filip; Benková, Eva; Van Der Straeten, Dominique (New Phytologist)
Germination of Arabidopsis seeds in darkness induces apical hook development, based on a tightly regulated differential growth coordinated by a multiple hormone cross-talk. Here, we endeavoured to clarify the function of brassinosteroids (BRs) and cross-talk with ethylene in hook development. An automated infrared imaging system was developed to study the kinetics of hook development in etiolated Arabidopsis seedlings. To ascertain the photomorphogenic control of hook opening, the system was equipped with an automatic light dimmer. We demonstrate that ethylene and BRs are indispensable for hook formation and maintenance. Ethylene regulation of hook formation functions partly through BRs, with BR feedback inhibition of ethylene action. Conversely, BR-mediated extension of hook maintenance functions partly through ethylene. Furthermore, we revealed that a short light pulse is sufficient to induce rapid hook opening. Our dynamic infrared imaging system allows high-resolution, kinetic imaging of up to 112 seedlings in a single experimental run. At this high throughput, it is ideally suited to rapidly gain insight in pathway networks. We demonstrate that BRs and ethylene cooperatively regulate apical hook development in a phase-dependent manner. Furthermore, we show that light is a predominant regulator of hook opening, inhibiting ethylene- and BR-mediated postponement of hook opening.

Cytokinin controls polarity of PIN1-dependent Auxin transport during lateral root organogenesis - Marhavy, Peter; Duclercq, Jérôme; Weller, Benjamin; Feraru, Elena; Bielach, Agnieszka; Offringa, Remko; Friml, Jirí; Schwechheimer, Claus; Murphy, Angus; Benková, Eva (Current Biology)
The plant hormones auxin and cytokinin mutually coordinate their activities to control various aspects of development [1-9], and their crosstalk occurs at multiple levels [10, 11]. Cytokinin-mediated modulation of auxin transport provides an efficient means to regulate auxin distribution in plant organs. Here, we demonstrate that cytokinin does not merely control the overall auxin flow capacity, but might also act as a polarizing cue and control the auxin stream directionality during plant organogenesis. Cytokinin enhances the PIN-FORMED1 (PIN1) auxin transporter depletion at specific polar domains, thus rearranging the cellular PIN polarities and directly regulating the auxin flow direction. This selective cytokinin sensitivity correlates with the PIN protein phosphorylation degree. PIN1 phosphomimicking mutations, as well as enhanced phosphorylation in plants with modulated activities of PIN-specific kinases and phosphatases, desensitize PIN1 to cytokinin. Our results reveal conceptually novel, cytokinin-driven polarization mechanism that operates in developmental processes involving rapid auxin stream redirection, such as lateral root organogenesis, in which a gradual PIN polarity switch defines the growth axis of the newly formed organ.

The influence of heat stress on auxin distribution in transgenic B napus microspores and microspore derived embryos - Dubas, Ewa; Moravčíková, Jana; Libantová, Jana; Matušíková, Ildikó; Benková, Eva; Zur, Iwona; Krzewska, Monika (Protoplasma)
Plant embryogenesis is regulated by differential distribution of the plant hormone auxin. However, the cells establishing these gradients during microspore embryogenesis remain to be identified. For the first time, we describe, using the DR5 or DR5rev reporter gene systems, the GFP- and GUS-based auxin biosensors to monitor auxin during Brassica napus androgenesis at cellular resolution in the initial stages. Our study provides evidence that the distribution of auxin changes during embryo development and depends on the temperature-inducible in vitro culture conditions. For this, microspores (mcs) were induced to embryogenesis by heat treatment and then subjected to genetic modification via Agrobacterium tumefaciens. The duration of high temperature treatment had a significant influence on auxin distribution in isolated and in vitro-cultured microspores and on microspore-derived embryo development. In the “mild” heat-treated (1 day at 32 °C) mcs, auxin localized in a polar way already at the uni-nucleate microspore, which was critical for the initiation of embryos with suspensor-like structure. Assuming a mean mcs radius of 20 μm, endogenous auxin content in a single cell corresponded to concentration of 1.01 μM. In mcs subjected to a prolonged heat (5 days at 32 °C), although auxin concentration increased dozen times, auxin polarization was set up at a few-celled pro-embryos without suspensor. Those embryos were enclosed in the outer wall called the exine. The exine rupture was accompanied by the auxin gradient polarization. Relative quantitative estimation of auxin, using time-lapse imaging, revealed that primordia possess up to 1.3-fold higher amounts than those found in the root apices of transgenic MDEs in the presence of exogenous auxin. Our results show, for the first time, which concentration of endogenous auxin coincides with the first cell division and how the high temperature interplays with auxin, by what affects delay early establishing microspore polarity. Moreover, we present how the local auxin accumulation demonstrates the apical–basal axis formation of the androgenic embryo and directs the axiality of the adult haploid plant.

Allopolyploid origin of the Balkan endemic Ranunculus wettsteinii (Ranunculaceae) inferred from nuclear and plastid DNA sequences - Cires Rodriguez, Eduardo; Baltisberger, Matthias; Cuesta, Candela; Vargas, Pablo; Prieto, José (Organisms Diversity and Evolution)
The Balkan Peninsula, characterized by high rates of endemism, is recognised as one of the most diverse and species-rich areas of Europe. However, little is known about the origin of Balkan endemics. The present study addresses the phylogenetic position of the Balkan endemic Ranunculus wettsteinii, as well as its taxonomic status and relationship with the widespread R. parnassiifolius, based on nuclear DNA (internal transcribed spacer, ITS) and plastid regions (rpl32-trnL, rps16-trnQ, trnK-matK and ycf6-psbM). Maximum parsimony and Bayesian inference analyses revealed a well-supported clade formed by accessions of R. wettsteinii. Furthermore, our phylogenetic and network analyses supported previous hypotheses of a likely allopolyploid origin for R. wettsteinii between R. montenegrinus and R. parnassiifolius, with the latter as the maternal parent.

Role of the Arabidopsis PIN6 auxin transporter in auxin homeostasis and auxin-mediated development - Cazzonelli, Christopher; Vanstraelen, Marleen; Simon, Sibu; Yin, Kuide; Carron Arthur, Ashley; Nisar, Nazia; Tarle, Gauri; Cuttriss, Abby; Searle, Iain; Benková, Eva; Mathesius, Ulrike; Masle, Josette; et al. (PLoS One)
Plant-specific PIN-formed (PIN) efflux transporters for the plant hormone auxin are required for tissue-specific directional auxin transport and cellular auxin homeostasis. The Arabidopsis PIN protein family has been shown to play important roles in developmental processes such as embryogenesis, organogenesis, vascular tissue differentiation, root meristem patterning and tropic growth. Here we analyzed roles of the less characterised Arabidopsis PIN6 auxin transporter. PIN6 is auxin-inducible and is expressed during multiple auxin-regulated developmental processes. Loss of pin6 function interfered with primary root growth and lateral root development. Misexpression of PIN6 affected auxin transport and interfered with auxin homeostasis in other growth processes such as shoot apical dominance, lateral root primordia development, adventitious root formation, root hair outgrowth and root waving. These changes in auxin-regulated growth correlated with a reduction in total auxin transport as well as with an altered activity of DR5-GUS auxin response reporter. Overall, the data indicate that PIN6 regulates auxin homeostasis during plant development.

An auxin transport mechanism restricts positive orthogravitropism in lateral roots - Rosquete, Michel; Von Wangenheim, Daniel; Marhavy, Peter; Barbez, Elke; Stelzer, Ernst; Benková, Eva; Maizel, Alexis; Kleine Vehn, Jürgen (Current Biology)
As soon as a seed germinates, plant growth relates to gravity to ensure that the root penetrates the soil and the shoot expands aerially. Whereas mechanisms of positive and negative orthogravitropism of primary roots and shoots are relatively well understood [1-3], lateral organs often show more complex growth behavior [4]. Lateral roots (LRs) seemingly suppress positive gravitropic growth and show a defined gravitropic set-point angle (GSA) that allows radial expansion of the root system (plagiotropism) [3, 4]. Despite its eminent importance for root architecture, it so far remains completely unknown how lateral organs partially suppress positive orthogravitropism. Here we show that the phytohormone auxin steers GSA formation and limits positive orthogravitropism in LR. Low and high auxin levels/signaling lead to radial or axial root systems, respectively. At a cellular level, it is the auxin transport-dependent regulation of asymmetric growth in the elongation zone that determines GSA. Our data suggest that strong repression of PIN4/PIN7 and transient PIN3 expression limit auxin redistribution in young LR columella cells. We conclude that PIN activity, by temporally limiting the asymmetric auxin fluxes in the tip of LRs, induces transient, differential growth responses in the elongation zone and, consequently, controls root architecture.

Auxin reflux between the endodermis and pericycle promotes lateral root initiation - Marhavy, Peter; Vanstraelen, Marleen; De Rybel, Bert; Zhaojun, Ding; Bennett, Malcolm; Beeckman, Tom; Benková, Eva (EMBO Journal)
Lateral root (LR) formation is initiated when pericycle cells accumulate auxin, thereby acquiring founder cell (FC) status and triggering asymmetric cell divisions, giving rise to a new primordium. How this auxin maximum in pericycle cells builds up and remains focused is not understood. We report that the endodermis plays an active role in the regulation of auxin accumulation and is instructive for FCs to progress during the LR initiation (LRI) phase. We describe the functional importance of a PIN3 (PIN-formed) auxin efflux carrier-dependent hormone reflux pathway between overlaying endodermal and pericycle FCs. Disrupting this reflux pathway causes dramatic defects in the progress of FCs towards the next initiation phase. Our data identify an unexpected regulatory function for the endodermis in LRI as part of the fine-tuning mechanism that appears to act as a check point in LR organogenesis after FCs are specified.

Modeling framework for the establishment of the apical-basal embryonic axis in plants - Wabnik, Krzysztof T; Robert, Hélène; Smith, Richard; Friml, Jirí (Current Biology)
The apical-basal axis of the early plant embryo determines the body plan of the adult organism. To establish a polarized embryonic axis, plants evolved a unique mechanism that involves directional, cell-to-cell transport of the growth regulator auxin. Auxin transport relies on PIN auxin transporters [1], whose polar subcellular localization determines the flow directionality. PIN-mediated auxin transport mediates the spatial and temporal activity of the auxin response machinery [2-7] that contributes to embryo patterning processes, including establishment of the apical (shoot) and basal (root) embryo poles [8]. However, little is known of upstream mechanisms guiding the (re)polarization of auxin fluxes during embryogenesis [9]. Here, we developed a model of plant embryogenesis that correctly generates emergent cell polarities and auxin-mediated sequential initiation of apical-basal axis of plant embryo. The model relies on two precisely localized auxin sources and a feedback between auxin and the polar, subcellular PIN transporter localization. Simulations reproduced PIN polarity and auxin distribution, as well as previously unknown polarization events during early embryogenesis. The spectrum of validated model predictions suggests that our model corresponds to a minimal mechanistic framework for initiation and orientation of the apical-basal axis to guide both embryonic and postembryonic plant development.

Cytokinin cross talking during biotic and abiotic stress responses - O'Brien, José; Benková, Eva (Frontiers in Plant Science)
As sessile organisms, plants have to be able to adapt to a continuously changing environment. Plants that perceive some of these changes as stress signals activate signaling pathways to modulate their development and to enable them to survive. The complex responses to environmental cues are to a large extent mediated by plant hormones that together orchestrate the final plant response. The phytohormone cytokinin is involved in many plant developmental processes. Recently, it has been established that cytokinin plays an important role in stress responses, but does not act alone. Indeed, the hormonal control of plant development and stress adaptation is the outcome of a complex network of multiple synergistic and antagonistic interactions between various hormones. Here, we review the recent findings on the cytokinin function as part of this hormonal network. We focus on the importance of the crosstalk between cytokinin and other hormones, such as abscisic acid, jasmonate, salicylic acid, ethylene, and auxin in the modulation of plant development and stress adaptation. Finally, the impact of the current research in the biotechnological industry will be discussed.

Systems approaches to study root architecture dynamics - Cuesta, Candela; Wabnik, Krzysztof T; Benková, Eva (Frontiers in Plant Science)
The plant root system is essential for providing anchorage to the soil, supplying minerals and water, and synthesizing metabolites. It is a dynamic organ modulated by external cues such as environmental signals, water and nutrients availability, salinity and others. Lateral roots (LRs) are initiated from the primary root post-embryonically, after which they progress through discrete developmental stages which can be independently controlled, providing a high level of plasticity during root system formation. Within this review, main contributions are presented, from the classical forward genetic screens to the more recent high-throughput approaches, combined with computer model predictions, dissecting how LRs and thereby root system architecture is established and developed.